Enantioselective construction of spiro-tetrahydroquinoline scaffolds through asymmetric catalytic cascade reactions. Issue 21 (22nd February 2022) - Zhang, Jia-Lu; Ma, Rui; Zhao, Huan-Huan; Xu, Peng-Fei
Abstract : We have successfully merged a spiro-tetrahydroquinoline with spiro-benzofuranone into a single new scaffold through asymmetric catalytic cascade reaction with good yields, and high enantioselectivities and diastereoselectivities. Abstract : An efficient and concise strategy has been successfully developed for merging spiro-tetrahydroquinoline with spiro-benzofuranone into a single new skeleton through asymmetric catalytic cascade reactions catalyzed by quinine-derived chiral bifunctional squaramide organocatalysts. In this approach, differently substituted spiro-tetrahydroquinoline derivatives were smoothly obtained with high yields, and excellent diastereoselectivities and enantioselectivities (up to 99% yield, up to >20 : 1 dr, up to >99% ee, 40 examples) under mild reaction conditions.